2014
DOI: 10.5455/gmj-30-45904
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in epilepsy and potential risk factors associated with non adherence in tertiary care teaching hospital in southwest Ethiopia

Abstract: Medication non-adherence to antiepileptic medications is detrimental to the perceived outcome of treatment. Non-adherence to medication regimen accounts for substantial worsening of disease, death and increased health care costs. In this study, we aimed to determine adherence rate to antiepileptic medications and identify the potential risk factors associated with non-adherence in Jimma University Specialized Hospital/JUSH. A hospital based cross-sectional study was conducted on 265 patients using patients sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
5
18
0
Order By: Relevance
“…A study conducted in Finland indicated the prevalence of AEDs nonadherence as 34% and nonadherence was higher in individuals who smoke cigarette and drink alcohol [11]. In sub-Saharan African countries, prevalence of antiepileptic drug nonadherence is significant which was about 67% in Nigeria, 54% in Kenya, and 37% in Ethiopia and financial factors were the significant predictors of nonadherence [8, 1214]. …”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Finland indicated the prevalence of AEDs nonadherence as 34% and nonadherence was higher in individuals who smoke cigarette and drink alcohol [11]. In sub-Saharan African countries, prevalence of antiepileptic drug nonadherence is significant which was about 67% in Nigeria, 54% in Kenya, and 37% in Ethiopia and financial factors were the significant predictors of nonadherence [8, 1214]. …”
Section: Introductionmentioning
confidence: 99%
“…(12). In the study conducted by Getachew et al (2014), it was concluded that the rate of the patients' adherence to medication regimen is low. The most important reason for non-adherence to medication program were forgetfulness, lack of information regarding the importance of the amount and frequency of medication use, and the decision to stop taking medication (13).…”
Section: Total Adherencementioning
confidence: 99%
“…In the study conducted by Getachew et al (2014), it was concluded that the rate of the patients' adherence to medication regimen is low. The most important reason for non-adherence to medication program were forgetfulness, lack of information regarding the importance of the amount and frequency of medication use, and the decision to stop taking medication (13). Considering the reasons for non-adherence, there is a need to increase the patient's knowledge on the importance of medication use and family training in order to accompany the patient (14).…”
Section: Total Adherencementioning
confidence: 99%
“…AEDs nonadherence will also lead to increase burden of inpatient and emergency department services (17,18). There was a negative relation between medication adherence and frequency of seizures.…”
Section: Introductionmentioning
confidence: 99%
“…The value of ''p''( p= proportion of prevalence) was taken as 36.8% of antiepileptic drug nonadherence from a study conducted in Jimma University specialized hospital, Southwest Ethiopia to estimate the sample size (17), total sample size for this study is 359. Then the total source of population are 725 that means less than 10,000; therefore it was used correction formula and by considering 10% non response rate, so final sample size 265.…”
Section: Sample Size Determination and Techniquementioning
confidence: 99%